To Nordic or not to Nordic? A different perspective with reason to appreciate Semitendinosus more than ever - Giakoumis (Sport Performance & Science Reports, 2020)
Vegemite or marmite, Messi or Ronaldo, Real Madrid or Barcelona, Nordics or no Nordics. These contentious debates continue to occur and will continue to occur for many years to come. But why Nordics versus no Nordics? Has thereever been a bigger debate about a single exercise? Has there been an exercise that has caused more arguments on Twitter or within a performance team as to whether they should be performed? The arguments around delayed onset muscle soreness (DOMS), the high volumes previously suggested and its non-functional nature continue to drive the discussions (1,2). With a recent systematic review (3) demonstrating a 51% reduction in hamstring injuries with the simple addition of the Nordic hamstring curl (NHC), it is hard for many to argue gainst the favourable outcome-based data that NHCs`provide. It further supports previous work that demonstrated the significant reduction in hamstring injury in those adhering to a prescribed large volume NHC program (1).